Value concepts of legal and prison security. (Journal of actual problems of jurisprudence, 2016)
This article examines the legal and prison security concerns of the penitentiary system in the Republic of Kazakhstan.In this ensuring security prison due to legal security prison legislation, which excludes the presence of a corruptionconflicting standards? Ensuring security prison due to legal security (certainty) prison legislation, which excludes the presence of a corruption-conflicting rules, spaces, etc. Propensity for corruption, which consists in established lenii enforcers unreasonably wide margin of discretion and opportunities unreasonable application of exceptions to the rulesing, ensuring prison security can be defined as DELENA reality legality, humanism, democracy, subjects projective processes in the practice of penance and execution serving arrest and criminal penalties. In fact, the software security penitentiary ary is a manifestation and embodiment of humanitarian ism and repentance, and the actual detention and humanism has provided security prison.
Keywords: prison security; penal law; educational and correctional work; labor; convicted; imprisonment